A comprehensive study on geometric, topological and fractal characterizations of pore systems in low-permeability reservoirs based on SEM, MICP, NMR, and X-ray CT experiments. (May 2019) - Wu, Yuqi; Tahmasebi, Pejman; Lin, Chengyan; Zahid, Muhammad Aleem; Dong, Chunmei; Golab, Alexandra N.; Ren, Lihua
Abstract: Characterization of pore systems in subsurface systems is of great importance for predicting the properties of rocks and classifying the subsurface systems. Geometric features have been used widely for this aim, but topological characteristics of the pore structures are not studied much. In fact, accurate characteristics of pore space should comprise both its geometric and topological properties. In this paper, the above vital characteristics are comprehensively studied based on direct experimental results. Besides, previous studies aiming at linking fractal dimension analysis to pore space are often based on limited sources of information, which are the mercury injection capillary pressure (MICP) and nuclear magnetic resonance (NMR). In this paper, the scanning electron microscope (SEM), MICP, NMR, and X-ray computed tomography (X-ray CT) experiments are all used to characterize the geometric and topological properties of pore space of several low-permeability porous media. Based on our observations, the advantages and disadvantages of the above techniques in characterizing the pore structure are also summarized. Moreover, the differences of these three experiments are quantified using fractal dimension. The results indicate that the NMR technique is a promising tool for characterizing geometric features of pore systems as it can cover more details than other techniques. Most of geometric, topological, fractal and transport properties of pore space can be obtained from X-ray CT method, which is unique among all the methods. In addition, the 3D fractal dimensions of pore systems obtained from NMR is smaller than that from MICP, which is due more ultra-micropores captured by NMR that smooth the surface of the pore systems. Finally, a novel method constrained by a new pore shape factor for calculating the pore size from 2D images is proposed by which the pore-size distributions are compared more effectively. Highlights: Geometric and topological characteristics of the pore systems are analyzed. The morphology properties are studied based on SEM, MICP, NMR and X-ray CT techniques. Fractal dimension is calculated from MICP, NMR and X-ray CT data. A novel method constrained by pore shape factor for calculating the pore size from 2D images was proposed.